2017
DOI: 10.1007/s00226-017-0903-z
|View full text |Cite
|
Sign up to set email alerts
|

A generic platform for hyperspectral mapping of wood

Abstract: Sustainable use is essential to guarantee future availability of wood. Structural and chemical mapping can contribute to fit-for-purpose usage, as accurate and detailed knowledge of the material enables guided utilization and optimal performance of wood. The platform presented in this paper, illustrated on poplar disks for early selection, collects data in the NIR, visual and X-ray spectrum in maximum 30 min per wood disk. Flatbed scanning proves to be a cheap and fast technique to evaluate basic physical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…An example is the dual energy approach (scanning at two energies which improves differentiating between features, in this case water in wood) recently showcased for moisture mapping of wood [337]. Finally, multi-spectral and multi-modal workflows (SilviScan and DiscBot are examples) either by combination of several different cutting-edge equipment [338] for a combination of optical, X-ray, and NIR imaging) or by combination in a single machine (Laforce et al [339] combining X-ray, CT, and X-ray fluorescence) are currently being developed. NDE tools have presented new opportunities for tree breeding programs.…”
Section: Future Challenges and Opportunities For Nde Of Wood Propertiesmentioning
confidence: 99%
“…An example is the dual energy approach (scanning at two energies which improves differentiating between features, in this case water in wood) recently showcased for moisture mapping of wood [337]. Finally, multi-spectral and multi-modal workflows (SilviScan and DiscBot are examples) either by combination of several different cutting-edge equipment [338] for a combination of optical, X-ray, and NIR imaging) or by combination in a single machine (Laforce et al [339] combining X-ray, CT, and X-ray fluorescence) are currently being developed. NDE tools have presented new opportunities for tree breeding programs.…”
Section: Future Challenges and Opportunities For Nde Of Wood Propertiesmentioning
confidence: 99%
“…In this regard, hyperspectral near-infrared (NIR) imaging is an appropriate method to study structural and chemical changes within the wood [10][11][12]. The NIR images are three-way datasets, where two dimensions render the spatial mapping of the chemical analytes, while the third dimension contains spectral variables.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Similarly, wood-related NIR-and SWIR-HSI research has been increasingly reported in the literature, where cameras have been used to examine various spectral and spatial properties and variations of wood materials. Applications include the estimation of physical and mechanical properties of radial strips [11][12][13][14][15] and lumber [16][17][18] as well as the detection of compression wood [19,20], tension wood [21] and resin defects [22]. A common area of research has been the estimation of wood moisture content [23][24][25], and associated research includes an investigation of changes in the spatial distribution of water when wood is dried [20].…”
Section: Introductionmentioning
confidence: 99%